2008
DOI: 10.1590/s0080-62342008000300011
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para a não adesão ao tratamento com terapia antiretroviral altamente eficaz

Abstract: RESUMENObjetivo del estudio: medir la prevalencia por falta de seguimiento al tratamiento antiretroviral altamente eficaz (HAART) en pacientes con SIDA; identificar si algunos factores relacionados en la bibliografía se encuentran asociados con la falta de seguimiento; establecer el valor preditivo de los factores asociados con la falta de seguimiento al HAART. Para lo cual fue realizado un estudio analitico de prevalencia (N=60), considerándose los tres días anteriores a la entrevista, donde aquellos paciente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
1
15
0
12
Order By: Relevance
“…In adherence to drug therapy for diabetic patients, it was found that adherence was greater in elderly subjects (26) . Conversely, adherence to antiretroviral therapy was higher in younger subjects (17) . However, data regarding adherence of the elderly to health treatments suggest that age has not been consistently associated with adherence (27) .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In adherence to drug therapy for diabetic patients, it was found that adherence was greater in elderly subjects (26) . Conversely, adherence to antiretroviral therapy was higher in younger subjects (17) . However, data regarding adherence of the elderly to health treatments suggest that age has not been consistently associated with adherence (27) .…”
Section: Discussionmentioning
confidence: 86%
“…Regarding education, no significant relationship with regard to the stages of adherence was observed, contrary to previous literature. In this regard, one previous study suggested that subjects with higher education were more adherent to antiretroviral therapy than non-educated patients (17) . Similarly, low literacy has been associated with decreased adherence to therapy (18) .…”
Section: Discussionmentioning
confidence: 95%
“…About the number of pills taken per day, 187 (87%) patients take between one and four; the largest number of pills taken per day was 12. The total number of pills can increase inappropriate adherence rates by 12% for every 10 pills 12 . As regards the dosage, this ranged between one and three times per day, with a prevalence of patients who need to take the medication twice a day, corresponding to 163 (75.8%).…”
Section: Resultsmentioning
confidence: 99%
“…Essas pessoas foram também as que apresentaram maior percepção do suporte social fornecido. Dados de outros estudos realizados no Brasil apontam que a raça negra possui renda inferior quando comparada às demais, além de possuir risco de não adesão [20,21], evidenciando a necessidade do suporte instrumental para a manutenção do seu TARV.…”
Section: Discussionunclassified